Muḥāwalāt Fī Taisīr Ta'līm al-Nahw - Abdul Basith (Alsinatuna)
Nahwu becomes the most debated discourse in the Arabic language teaching. There are so many problems appear both in the case of the learning material and the learning methods. This article describes those problems by elaborating the causes of learning difficulties in Nahwu. One of the problems comes from the existence of excessive ‘amil and ‘illat. It reveals a judgment that Nahwu has been combined with philosophy. Consequently, there are some learners who judge that learning Arabic is difficult. Therefore, this article also presents the easy ways in learning Nahwu, both given by classic ulama and modern linguists. One of the efforts done by classic ulama is by reviewing the theory of ‘amil, while the modern linguists try to expand the concept of Nahwu so that it is not limited to i’rab only.